Syndrome of inappropriate antidiuretic hormone secretion following bipolar transurethral resection of the prostate. (March 2022) - Rezvani, Sean; Taktak, Samih; Brough, Richard
Syndrome of inappropriate antidiuretic hormone secretion following minimally invasive surgery is extremely rare, having only been reported in a handful of cases. We present the second documented case of syndrome of inappropriate antidiuretic hormone secretion following transurethral resection in an 80-year-old male undergoing bipolar transurethral resection of the prostate for bladder outflow obstruction. Level of evidence: 5